Design of Low Alkali Activator Geopolymer Concrete Mixtures - Setia Romadhon, Eri; Antonius, Antonius; Sumirin, Sumirin (ASTONJADRO, 2022)
This paper presents the results of research on the design of geopolymer concrete mixes. The main objective of this research is to develop an efficient and easy design of low-alkaline activator geopolymer concrete mixture, which until now has been the biggest obstacle in the use of geopolymer concrete. The variables reviewed were the amount of alkaline activator was quite low at 4%, room temperature and 60oC ratio of alkaline activator/fly ash (AAS/FA) were 0.35, 0.4, 0.5, 0.6. The test results show the parameters of geopolymer concrete with low alkali activator 4%, sodium silicate/sodium hydroxide ratio 2.5%, sodium hydroxide molarity 14M, type F fly ash and the discovery of the relationship model of compressive strength and the ratio of alkali activator/fly ash with a very high correlation as basic development of geopolymer concrete mix design. The design of the geopolymer concrete mix developed is easy because it is application-based and efficient because it only requires 4% alkaline activator.